2011
DOI: 10.1007/s13089-011-0062-7
|View full text |Cite
|
Sign up to set email alerts
|

Extreme musculo-skeletal ultrasound: training of non-physicians in the Arctic Circle

Abstract: Objective The purpose of this study was to compare if non-physician, inexperienced ultrasound subjects can take quality diagnostic images after watching a brief educational video and using reference cue cards (autonomous group) versus taking ultrasound images with expert guidance using a satellite connection. Methods Six non-medical, inexperienced ultrasound subjects from a rural area (Arctic Circle) obtained ultrasound images of target anatomic regions using a portable ultrasound device after receiving expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Using such a system, McBeth et al conducted a series of trials with the assistance of healthy volunteers at a variety of remote sites to demonstrate the feasibility and applicability of these techniques conducted primarily over a smartphone [18, 19]. Other investigators have also utilized a variety of commercial video-streaming devices to transmit real-time streaming ultrasound images over either the internet [33] or satellite transmission [34, 35], with potential remote guidance potentially conducted by telephone or without a video camera depiction of the user [34, 35]. …”
Section: The Remote Transmission and Interpretation Of Ultrasound:mentioning
confidence: 99%
“…Using such a system, McBeth et al conducted a series of trials with the assistance of healthy volunteers at a variety of remote sites to demonstrate the feasibility and applicability of these techniques conducted primarily over a smartphone [18, 19]. Other investigators have also utilized a variety of commercial video-streaming devices to transmit real-time streaming ultrasound images over either the internet [33] or satellite transmission [34, 35], with potential remote guidance potentially conducted by telephone or without a video camera depiction of the user [34, 35]. …”
Section: The Remote Transmission and Interpretation Of Ultrasound:mentioning
confidence: 99%
“…1,5,6 Although these initial efforts created the field of real-time RTMUS, ongoing efforts have attempted to simplify and spin-off the technology/ technique for terrestrial use. 7,8 Accordingly, we report the first utilization of a novel simplified cost-effective RTMUS to mentor inexperienced health professionals to perform advanced bedside ultrasound exams after tube thoracostomy (TT) removal.…”
Section: Introductionmentioning
confidence: 99%
“…Farsi D et al, suggested that cardiac ultrasound by trained emergency medicine residents is comparable to echocardiography performed by cardiologists and it could be used as a reliable tool and screening test for initial testing of patients suspected of cardiac abnormalities in the acute setting (5). Two nonrandomized studies concluded that non-radiologist doctors could use of portable ultrasonography, effectively, in musculoskeletal disorders after a short training session (6,7). This shows that bedside ultrasonography would be widely used especially in emergencies.…”
Section: Discussionmentioning
confidence: 99%